Aplikasi Penukaran Dan Penampungan Minyak Jelantah - Yus Jayusman; Intan Annisa Nur Azizah (Jurnal Bangkit Indonesia, 2025)
Used cooking oil, or waste cooking oil, is often discarded and becomes waste that can harm the environment if not properly managed. Currently, its collection and management are still manual and inefficient, leading to issues such as supply imbalances and reporting delays. This research aims to develop an application that facilitates the exchange and storage of waste cooking oil between residents and collectors, addressing the challenges of manual processes and reducing environmental impact. Using an object-oriented approach (OOP) and the prototype method, this study involves data collection, software development, and evaluation of the impact of improved management on the quality of processed oil and the sustainability of the waste oil processing industry. The outcome is expected to provide an efficient and environmentally friendly solution for waste cooking oil management and also can simplify the process of collecting used cooking oil, accelerate automatic recording of exchange transactions, and improve the efficiency and regularity of data management. Therefore, this application can be an effective and environmentally friendly digital solution to support sustainable used cooking oil management.